Psilocybin-Mediated Attenuation of Gamma Band Auditory Steady-State Responses (ASSR) Is Driven by the Intensity of Cognitive and Emotional Domains of Psychedelic Experience - Viktorin, Vojtěch; Griškova-Bulanova, Inga; Voicikas, Aleksandras; Dojčánová, Dominika; Zach, Peter; Bravermanová, Anna; Andrashko, Veronika; Tylš, Filip; Korčák, Jakub; Viktorinová, Michaela; Koudelka, Vlastimil; Hájková, Kateřina; et al. (Journal of personalized medicine, 2022)
Psilocybin is a classical serotoninergic psychedelic that induces cognitive disruptions similar to psychosis. Gamma activity is affected in psychosis and is tightly related to cognitive processing. The 40 Hz auditory steady-state responses (ASSR) are frequently used as indicators to test the ability to generate gamma activity. Based on previous literature, we studied the impact of psilocybin on 40 Hz ASSR in healthy volunteers. The study was double blind and placebo controlled with a crossover design. A sample of 20 healthy subjects (10M/10F) received psilocybin orally 0.26 mg/kg or placebo. Participants were measured four times in total, one time before ingestion of psilocybin/placebo and one time after ingestion, during the peak of intoxication. A series of 500 ms click trains were used for stimulation. Psilocybin induced a psychedelic effect and decreased 40 Hz ASSR phase-locking index compared to placebo. The extent of the attenuation was related to Cognition and Affect on the Hallucinogen Rating Scale. The current study shows that psilocybin lowers the synchronization level and the amplitude of 40 Hz auditory steady-state responses, which yields further support for the role of gamma oscillations in cognitive processing and its disturbance.
Keywords: EEG; psychedelics; psilocybin; model of psychosis; serotonin; auditory steady-state response